Which Entrepreneurs are Coachable and Why? - Bryan, Kevin A.; Tilcsik, András; Zhu, Brooklynn (American Economic Review, 2017)
Is coachability a usable concept for startups? Using a dataset on high-growth startups in a prominent university incubator, we show that firm characteristics do predict which firms are likely to follow advice but that these “coachable” firms are not more likely to achieve positive outcomes. The reason is that advice may be rejected either because the firm is stubborn and uncoachable, or because the firm possesses capabilities related to the advice which is hard for outsiders to observe.